Assessing benefits and consequences of water conservation and fit for purpose water systems - Patel, Saloni N., author; Sharvelle, Sybil, advisor; Arabi, Mazdak, committee member; Nelson, Tracy, committee member (Colorado State University. Libraries, 2020)
Rising population accompanied with urbanization is increasingly challenging the resilience and capacity of traditional water management system. The migration of the human population to urban areas has given birth to sprawling new developments and re-developments which poses serious challenges to conserve and manage water. Water managers and policy makers are faced with an arduous task to enhance conventional water management systems by implementing Integrated Urban Water Management and hybrid centralized-decentralized systems. To enable informed decisions on water demand management strategies based on water demand reduction, cost, energy savings, etc., understanding benefits and consequences is of utmost importance. Benefits and consequences of water conservation and reuse are seldom considered while making quantitative decisions, mainly due to lack of supporting data or methodology. This research fills this knowledge gap by providing methodology on identifying, developing and quantifying a set of indicators that measure performance for water demand reduction strategies including conservation strategies and use of alternate water sources (i.e., fit for purpose water) in triple bottom line (TBL) categories. Literature review, triple bottom line (TBL) evaluation, and Multi-Criteria Decision Analyses (MCDA) were used to develop a set of indicators to assess water demand reduction strategies. To demonstrate the use of indicators to inform water management decisions, TBL indicator analysis was performed on Globeville-Elyria-Swansea (GES) community in Denver, Colorado using Integrated Urban Water Model (IUWM). The results from TBL indicator analysis suggests that use of stormwater performed well across all indicator categories, it achieved high water demand reduction, was energy efficient and also publicly accepted. Further cost comparison and MCDA scores revealed, Stormwater for Potable & Irrigation as the top performing end use. Use of stormwater as a supply has potential for large reduction in demand for traditional supplies and also offers notable social and environmental benefits. Water rights issues and costs remain barriers for adoption of this practice that need to be overcome to realize the benefits.